2020
DOI: 10.1177/2473011420s00051
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of a Multicenter Prospective Randomized Trial: Traditional Modified Brostrom versus InternalBrace™ Augmentation

Abstract: Category: Sports; Ankle; Arthroscopy Introduction/Purpose: The modified Brostrom (MB) procedure has long been the mainstay for the treatment of chronic lateral ankle instability (CLAI) despite concerns about the strength of the repair. Recently, the InternalBraceTM (IB) has emerged as augmentation for this repair. The clinical benefit of such augmentation has yet to be established. The purpose of this study is to determine whether or not IB augmentation provides an advantage over the traditional MB. The prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Of note, studies are currently being conducted evaluating the feasibility of early or accelerated rehabilitation associated with augmented modified Broström procedures, as previously discussed. One study by Kulwin et al has demonstrated positive preliminary results regarding early rehabilitation after augmented Broström versus tradition modified Broström procedures 45,46 .…”
Section: Postoperative Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, studies are currently being conducted evaluating the feasibility of early or accelerated rehabilitation associated with augmented modified Broström procedures, as previously discussed. One study by Kulwin et al has demonstrated positive preliminary results regarding early rehabilitation after augmented Broström versus tradition modified Broström procedures 45,46 .…”
Section: Postoperative Managementmentioning
confidence: 99%
“…The Visual Analog Scale-Foot and Ankle. A patient-reported outcome measure for foot and ankle disorders 9,[43][44][45][46][47][48] .…”
Section: Cait Assists In Differentiationmentioning
confidence: 99%